DISTRIBUIÇÃO E FRACIONAMENTO DE METAIS EM SOLOS DO DISTRITO INDUSTRIAL DE SÃO LUÍS DO MARANHÃO - Robson, Alessio Costa (2014)
The geochemical fractions of Cd, Pb, Cu, Cr, Ni, Zn were determined according to the protocol developed by the Comunnity Bureau of Reference (BCR). The fractions of the protocol are divided into exchangeable (F1), reducible (F2), oxidisable (F3). A new fraction, the residual (F4), was included in the fractionation. The concentration of metals was determined by atomic emission spectrometry by inductively coupled plasma (ICP-OES). In addition, a mobility experiment was conducted by spiking a standard solution of metals to soils and subsequent application of the BCR protocol. The results of fractionation in the original soils detected only the presence of Pb, distributed in exchangeable (F1) and residual fractions (F4), indicating that soils are not contaminated. The mobility experiment showed that added metals in soils were retained in the fractions F1 and F3. Most acid soils have lower metal immobilization metals in fraction F1 (r2 = 0.99). The decreasing order of metals in each fraction contaminated soils was: F1 (55.3%)> F3 (18.75%)> F2 (6.35%). The application of principal component analysis (PCA) identified that the Cr showed higher affinity to organic fraction (F3), followed by Cu. The soils of the industrial district do not have values that offer risk to the ecosystem. In turn, these soils, due to its acidity and low organic matter content, provide unfavorable conditions to metal retention, favoring leaching in case of eventual contamination.